Model of Local Wisdom Education in The Ancient Sundanese Manuscript Sanghyang Siksa Kandang Karesian 1518 AD - Koswara, Dedi; Pandu Hyangsewu; Danan Darajat; Zulfikar Alamsyah (CV. Goresan Pena, 2024)
This study aims to describe the educational values of local wisdom of dasakreta, dasaindria, dasakalesa, dasamarga, dasapasanta, and dasaprebakti which are covered with the grand concept of tri tangtu di bumi (three provisions on earth; tangtu telu), and aims to develop a learning model based on local wisdom education (ethnopedagogy) from the ancient Sundanese manuscript Sanghyang Siksa Kandang Karesian (1518 AD). The method applied in this study is a descriptive method of critical analysis of the manuscript with a qualitative approach. The results showed that the values of local wisdom education in the ancient Sundanese manuscript of Sanghyang Siksa Kandang Karesian 1518 AD are closely related to the purpose of life and the postulate of the Sundanese people, namely inhale bagja, safe, tingtrim, ngahenang-ngahening, subul darajat, ngeunah angen-ngeunah angeun, sampurna world ahérat, hurip, sane, cageur, bageur, true, smart, honest, ludeung, silih asih, silih asah, silih nurturing, and sineger tengah. Furthermore, from this research, a set of ethnopedagogical teaching models based on the ancient Sundanese manuscript Sanghyang Siksa Kandang Karesian was produced in the form of learning syntax.